PENGARUH IMPLEMENTASI TEKNOLOGI INFORMASI DAN KUALITAS PELAYANAN JASA TERHADAP KEPUASAN PELANGGAN PADA PT. PLN BATAM - Narti Eka Putria (Universitas Putera Batam, 2013)
Customers PLN Batam continues to increase, so it is necessary technological tools to assist the process of improving customer service, poor quality of their services led to many customers complaining against PLN Batam services. Customers expect satisfaction with service PLN Batam quality products provided to customers are not in accordance with the wishes of the customer, so that customers feel aggrieved, it is necessary to apply information technology, the quality of service that the company's goal is achieved, Managed poorly, it can lead to miscommunication occurred between the PLN and the Government, because PLN is a limited liability company. The purpose of this study was to obtain an overview of the implementation of Informat technology in providing information needed for customer PT. PLN Batam, and gain an overview of the services provided to the customer PT. PLN Batam. To obtain an overview of customer satisfaction with PT. PLN Batam, to memperolehgambaran implementation of Information Technology to customer satisfaction PT. PLN Batam. To find out how much the level of quality services that include Tangible, realibility, Responsiveness, Assurance, and Empathy towards customer satisfaction PT. PLN Batam. Methods The study design using descriptive and correlation. Descriptive method is a type of research that provides an overview or description of a situation as clearly as possible without any treatment of the studied projects. While the study design korelasil, useful for understanding behavior, whether it is human behavior or other living things, or it could be the behavior of objects that are the objects of research, can be done by looking at whether a particular variable on the object to be examined relating to certain other variables. The findings of this study to get the results that the implementation of information technology to provide accurate information to customers PT. PLN, as well as the quality of services provided by PT. PLN Batam to qualified customers at this time, if eligible implementation of Information Technology. And if all the independent variables are met it will increase customer satisfaction PT. PT. PLN Batam according to the value of contributions, so the customer PT. PLN Batam are satisfied with the implementation of information technology and quality services applied in PLN Batam.